COVID-19 and environmental racism: Challenges and recommendations - Njoku, Anuli (European Journal of Environment and Public Health, 2021)
Keywords: dept.pch; peer-reviewed

COVID-19 and Health Disparities: Opportunities for Public Health Curriculum Enhancement - Njoku, Anuli (COVID-19 and Higher Education in the Global Context, 2022)
COVID-19, the pandemic of highly contagious respiratory disease, presents a global public health emergency. The COVID-19 pandemic has increased awareness of the role of public health and its professionals in responding to the pandemic. Racial and ethnic minority groups in the United States are more likely to contract and die from COVID-19 versus Whites, highlighting health disparities. Higher education schools and programs in public health can help prepare students to address this global pandemic through expanded curriculum on social determinants of health disparities in COVID-19 outcomes, teachings on implicit bias and anti-racism, interprofessional education, and practice-based learning. Moreover, eliminating health disparities is a leading public health priority in the United States and can help attain the World Health Organization goal of achieving health equity. This chapter highlights the need for public health curriculum that outlines strategies to address racial and ethnic disparities in COVID-19 to prepare and motivate a future healthcare workforce. How to cite this chapter: Njoku, A. (2022). COVID-19 and health disparities opportunities for public health curriculum enhancement. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 139-153). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/
Keywords: dept.pch; ⛔ No DOI found

Investigating the role of everyday material exposures on fertility - Njoku, Anuli (2026)
Keywords: Black women; Ethnic group; Fertility; Health care; Health equity; Maternal health; Pregnancy; Public health; Racism; dept.pch

Coping resources and self-care during COVID-19, police brutality, and social unrest - Njoku, Anuli (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
U.S. society has been gripped with dueling pandemics of racial and ethnic disparities in COVID-19 outcomes, highly publicized instances of police brutality against Black persons, and ensuing unrest to challenges these atrocities. In higher education, the rapid pivot response to COVID-19 with remote and virtual learning has also highlighted multiple levels of mental health trauma and disparities. There has also been vicarious trauma for Black women in academia who may have seen their family, friends, or loved ones reflected during increased media coverage of police brutality. This implores the need for effective strategies to mitigate these issues. This chapter discusses evidence-based strategies for Black women who navigate academia and teach during times of COVID-19 and social unrest. This chapter also proposes strategies for university leaders to consider alleviating cultural and racial gaps in the classroom or workplace and foster diversity and inclusion in academia.
Keywords: Academia; Black women; COVID-19; Higher education; Police brutality; Trauma; dept.pch

It’s a win-win: faculty-mentored research with students of color - Njoku, Anuli; Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
In addition to fueling health disparities, the COVID-19 pandemic has exacerbated inequities among faculty of color. COVID-19 has also taken a dramatic toll on college students’ mental health, with evident racial disparities. Gender inequality in research productivity has also been revealed, with women submitting fewer papers compared to men. This pandemic has created an opportunity, of sorts, to promote academic and career success among women and students of color in academia. Research has shown that mentorship and research opportunities improve chances for success among students of color in higher education. Faculty members can also progress personally and professionally from such collaborations. Still, students of color are not equally given opportunities to collaborate with faculty on research. This chapter shares perspectives and strategies from Black women faculty and graduate students regarding faculty-student research to promote academic and career success among faculty and students of color in academia.
Keywords: COVID-19; Faculty-mentored research; Mentoring; Student research; Students of color; dept.pch

Spaces to heal: providing the table and seats - Njoku, Anuli; Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Black, Indigenous, and People of Color (BIPOC) women faculty and administrators are breaking barriers, maintaining excellence, becoming award-winning scholars, and flourishing as experts in their fields. Still, they must survive while they thrive, grappling with insecurity, writer’s block, and imposter syndrome. Further examination prompts the realization that imposter syndrome may be a scapegoat for structural racism. Moreover, COVID-19 has created substantial health and financial tolls, fueled mental and emotional fatigue, and disrupted workplace productivity. These barriers caused by COVID-19 and structural racism inspire the courage to reassure, uplift, mentor, invite, and make collaborative spaces for BIPOC women to express feelings of vulnerability, unease, and, ultimately, hope. When seats are missing at the table, one can bring their own table and seats. In a field of often unforgiving critics, the authors provided underrepresented scholars the opportunity to promote authenticity and illuminate their voices. This chapter shares the authors’ reflections on being able to share the diverse and resilient perspectives of BIPOC women in academia.
Keywords: BIPOC women faculty; COVID-19; Imposter syndrome; Self-preservation; Sisterhood in the academy; dept.pch

Application of the Weathering Framework: Intersection of Racism, Stigma, and COVID-19 as a Stressful Life Event among African Americans - Wakeel, Fathima; Njoku, Anuli (Healthcare, 2021)
The disproportionate impact of coronavirus disease 2019 (COVID-19) on African American communities necessitates an increased focus on the intersectional roles of racism, stigma, and other social determinants of health in influencing disease and mortality risk. The Weathering Framework is applied to demonstrate the dynamic interrelationships between these factors and to conceptualize COVID-19 as a stressful life event that will have profound health implications over the life course for African Americans. Recommendations for population health research, interventions and policies aimed at reducing COVID-19 incidence and mortality, and mitigation of the long-term impacts of the pandemic on communities of color are discussed.
Keywords: Blacks/African Americans; COVID-19/coronavirus; dept.pch; health disparities; peer-reviewed; race/ethnicity; racism; social determinants of health; stigma; systemic racism

Navigating academia during COVID-19: perspectives and strategies from BIPOC women - Njoku, Anuli; Evans, Marian (Springer International Publishing, 2023)
Keywords: BIPOC faculty; Covid-19; Gender and Education; dept.pch; narrative inquiry; professional development; trauma

Covid-19 and environmental racism - Njoku, Anuli; Marcelin, Joseph (Springer eBooks, 2023)
Keywords: dept.pch

COVID-19, housing, and environmental injustice - Njoku, Anuli; Marcelin, Joseph (Hygiene, 2023)
Keywords: dept.pch

Consumption patterns of drinking water and its impact on public health - Njoku, Anuli; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Keywords: Consumption (sociology); Globe; Health equity; Investment (military); Population; Population health; Public health; Social determinants of health; Water supply; dept.pch

Health behavior and health promotion theories: application in environmental sciences and health - Njoku, Anuli; Molla, Azizur; Tohura, Sharaban (Handbook of Concepts in Health, Health Behavior and Environmental Health, 2025)
Keywords: Environmental health; Health behavior; Health promotion; Medicine; Nursing; Psychology; Public health; dept.pch

Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Police brutality against Blacks in the United States and ensuing protests: Implications for social distancing and Black health during COVID-19 - Njoku, Anuli; Ahmed, Yussuf; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2020)
The pandemic of respiratory disease spreading from person-to-person, named “coronavirus disease 2019” (abbreviated “COVID-19”), presents a public health emergency of international concern. This pandemic is occurring during renewed attention to the persistent issue of police brutality against Blacks in the United States. Protests have ensued to highlight perceived and observed injustice against minorities, particularly Black people. Concerns arise that these protests may complicate efforts to adhere to social distancing and increase risks of COVID-19 exposure among Black persons, who are already disproportionality affected by COVID-19 outcomes due to systemic barriers within the healthcare system and society. This article discusses police brutality against Blacks in the United States and subsequent protests, considerations for social distancing and racial disparities in health during COVID-19, and the need for policies to ensure fair and equitable enforcement of social distancing mandates. We also discuss the need for policies to improve access to COVID-19 testing, diagnosis, and management among underserved and minority communities. © 2020 Taylor & Francis Group, LLC.
Keywords: African Americans; COVID-19; Coronavirus; dept.pch; peer-reviewed; police brutality; public health

Changing the narrative: Structural barriers and racial and ethnic inequities in COVID-19 vaccination. - Njoku, Anuli; Joseph, Marcelin; Felix, Rochelle (International journal of environmental research and public health, 2021)
The COVID-19 pandemic has disproportionately affected racial and ethnic minority groups in the United States. Although a promising solution of the COVID-19 vaccination offers hope, disparities in access again threaten the health of these communities. Various explanations have arisen for the cause of disparate vaccination rates among racial and ethnic minorities, including discussion of vaccine hesitancy. Conversely, the role of vaccine accessibility rooted in structural racism as a driver in these disparities should be further explored. This paper discusses the impact of structural barriers on racial and ethnic disparities in COVID-19 vaccine uptake. We also recommend public health, health system, and community-engaged approaches to reduce racial disparities in COVID-19 disease and mortality. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: African American; Article; Black person; COVID-19; COVID-19 Vaccines; Coronavirus; Ethnic Groups; Health Status Disparities; Healthcare Disparities; Humans; Latino people; Minority Groups; Pandemics; SARS-CoV-2; SARS-CoV-2 vaccine; United States; Vaccination; access to computer; access to information; black population; communication barrier; coronavirus disease 2019; dept.pch; ethnic disparity; ethnic group; ethnic minority; health care access; health care disparity; health care system; health disparity; health literacy; health services; human; immigrant; infection prevention; internet access; language ability; mass immunization; minority group; mortality; outcome assessment; pandemic; peer-reviewed; public access; public health service; race difference; racial disparity; racism; social behavior; social determinants of health; social inequality; structural barrier; traffic and transport; vaccination

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

Self-Identification in Black, Red, Brown, and White: A clarion call to address medical racism in Native American communities - Boudreaux, Mary (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
This chapter provides a brief autobiographical account of her multiethnic and racial background as a Louisiana Creole in south Louisiana. The author points out that among all racial and ethnic groups in the United States, Indigenous people are the only ones that require some form of lineal Native American descent or blood quantum. The chapter provides an ancestry account of two American Indian tribes along the bayous of south Louisiana, the Chitimacha, and the United Houma Nation. While one federally recognized tribe has attempted to remove all relations to individuals of Black, Negro, or African American descent, the other has closed enrollment to new members (despite lineal descent), with the unifying factor among these communities being establishing progenitors. Finally, the author articulates how lack of access to resources related to issues such as COVID-19 has perpetuated the historical legacy of medical racism in tribal and underserved communities in the United States.
Keywords: COVID-19; Medical racism; Native American; Tribal communities; dept.edl

Leading in color in academia: a latinx chair’s experience of resiliency and hope - Reyes, Loida (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
On Wednesday, January 20, 2021, Kamala Harris broke through the gender and racial barrier that has kept men at the top ranks of American politics for over two centuries. This moment singlehandedly challenged the definition of leadership and who “fits” in that traditional model. Reyes examines the challenges and highlights three lessons of leading in color in academia today, being the first Latina to chair her department. Her journey reflects similar experiences of women of color who are burdened by the emotional toll that comes with being a part of systemic change, by virtue of leading while of color. To begin dismantling systemic racism and sexism, organizations must commit to addressing the issues head-on by reexamining policies, practices, and work environments that have perpetuated systemic inequalities. Greater supports are needed for women of color to be effective as their contributions are invaluable in achieving true systemic change.
Keywords: Academia; Hope; Latinx experiences; Resiliency; dept.swk

Giving Up Is Never an Option: Personal and Professional Development During COVID-19 - Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
COVID-19 brought me challenges and opportunities. I lost important people in this pandemic but also accomplished a lot. COVID-19 gave me a chance to soul search, grow, and develop. I blossomed into the woman I have always wanted to be but could not find. During it all, I was awarded my undergraduate degree, got accepted to a graduate program, received a new job, and bought my first car. With every blessing came a challenge, including health problems. Still, I persevered. Opportunities continue to present themselves and I seize them. Professional successes included publishing an article, presenting at a state public health conference, being featured in my university’s annual newsletter, and nailing my dream job! I got to “See Me!”, a woman of color coming from another country, accomplishing so much in a short span of time. This chapter details a true testimony and how giving up is not an option.
Keywords: COVID-19; Graduate students; Mental health; Resilience; dept.pch

ACEing the Black Trauma of the COVID-19 Pandemic - Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
When I first took the adverse childhood experiences (ACEs) quiz, I was overcome with the enormity of Black trauma contained in those ten questions. The quiz reflected my own story, as well as those of Black students, women, and families—traumas that were magnified by the impact of three pandemics: COVID-19, economic inequities, and systemic racism. The definition of trauma as “emotional responses to disastrous life events” like COVID-19 can have both short- and long-term health consequences throughout one’s lifespan. The impact of COVID-19 as Black trauma in my family will reverberate long after society heals from the last three years and moves toward living with COVID-19 symbiotically. It is imperative to recognize ACEs and their perpetual trauma to implement successful trauma-informed practices to counteract and undo the damaging effects of COVID-19 on our collective lives.
Keywords: ACEs quiz; Adverse childhood experiences; COVID-19; Trauma-informed practices; dept.pch

Environmental health disparities and maternal and child health: applying the life course approach - Wakeel, Fathima; Njoku, Anuli (Handbook of Social Sciences and Global Public Health, 2023)
Mounting evidence suggests that differential environmental exposures significantly contribute to a wide range of population health disparities. Adopting a life course approach to maternal and child health enables readers to uncover the mechanisms by which prenatal and early life environmental exposures potentially shape both short- and long-term physical and mental health outcomes. This chapter applies the life course approach to explore the adverse influences of environmental risk factors on maternal and child health. The following four case studies will be discussed: (1) the pervasive impacts of secondhand smoke; (2) the deleterious effects of lead exposure; (3) the development of asthma; and (4) the potential origins of autism spectrum disorder. The chapter also provides recommendations for programmatic and policy interventions to reduce the prevalence of four salient environmental hazards, including secondhand smoke, lead, air pollution, and pesticides, as well as proposed future directions in research regarding these exposures.
Keywords: Asthma; Autism spectrum disorder; Environmental health justice; Health equity; Lead exposure; Life course approach; Maternal and child health; Secondhand smoke exposure; dept.pch

Racial and ethnic disparities in cancer occurrence and outcomes in rural United States: a scoping review - Njoku, Anuli; Sawadogo, Wendemi; Frimpong, Princess (Cancer Control, 2024)
BackgroundCancer is the second-leading cause of death in the United States. Most studies have reported rural versus urban and Black versus White cancer disparities. However, few studies have investigated racial disparities in rural areas.ObjectiveWe conducted a literature review to explore the current state of knowledge on racial and ethnic disparities in cancer attitudes, knowledge, occurrence, and outcomes in rural United States.MethodsA systematic search of PubMed and Embase was performed. Peer-reviewed articles published in English from 2004-2023 were included. Three authors independently reviewed the articles and reached a consensus.ResultsAfter reviewing 993 articles, a total of 30 articles met the inclusion criteria and were included in the present review. Studies revealed that underrepresented racial and ethnic groups in rural areas were more likely to have low cancer-related knowledge, low screening, high incidence, less access to treatment, and high mortality compared to their White counterparts.ConclusionUnderrepresented racial and ethnic groups in rural areas experienced a high burden of cancer. Improving social determinants of health may help reduce cancer disparities and promote health.
Keywords: dept.pch; peer-reviewed

Comparing Environmental Policies to Reduce Pharmaceutical Pollution and Address Disparities - Desai, Meghana; Njoku, Anuli; Nimo-Sefah, Lillian (International Journal of Environmental Research and Public Health, 2022)
Pharmaceutical products, including active pharmaceutical ingredients and inactive ingredients such as packaging materials, have raised significant concerns due to their persistent input and potential threats to human and environmental health. Discourse on reducing pharmaceutical waste and subsequent pollution is often limited, as information about the toxicity of pharmaceuticals in humans is yet to be fully established. Nevertheless, there is growing awareness about ecotoxicity, and efforts to curb pharmaceutical pollution in the European Union (EU), United States (US), and Canada have emerged along with waste disposal and treatment procedures, as well as growing concerns about impacts on human and animal health, such as through antimicrobial resistance. Yet, the outcomes of such endeavors are often disparate and involve multiple agencies, organizations, and departments with little evidence of cooperation, collaboration, or oversight. Environmental health disparities occur when communities exposed to a combination of poor environmental quality and social inequities experience more sickness and disease than wealthier, less polluted communities. In this paper, we discuss pharmaceutical environmental pollution in the context of health disparities and examine policies across the US, EU, and Canada in minimizing environmental pollution.
Keywords: dept.pch; disparities; environmental policies; peer-reviewed; pharmaceutical pollution; pharmaceutical waste

Grow through what you go through - Ortiz, Chelsea L. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Being a millennial person-of-color in the twenty-first century is exhaustive in itself—adding the vulnerabilities of a global pandemic magnified that undertaking. As women, we bear the responsibilities of balancing our professional life with our family life; our role as a partner or friend with our role as an individual being; and our mental health with our social health. “Grow Through What You Go Through” explores the value of saying “Yes, I can do this too” when COVID-19 gave many a reason to say, “I’ve had enough.” Between being a supportive partner and family member to many who experienced financial and educational setbacks and being an important part of preparing the next set of future nurses to lead and excel during a global pandemic, COVID-19 enlightened my perspective on who I was at the start of COVID-19 and the person I would turn out to be by the end of it.
Keywords: COVID-19; Coping; Resilience; dept.nur

Lessons for My Daughters (Taught to Me by bell) - Hutchinson, Brandon L. A. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
As a tenured professor at a predominantly white institution (PWI), I am aware of the hardships we face in the academy; as a mother of three Black girls, a wife to a Black man, I am full. And yet, I must make space to see my own self clearly. Each day as a Black woman, I must set the intention to save my own life.
Keywords: Identity; Introspection; Self-care; dept.eng

Environment injustice and public health - Njoku, Anuli U.; Sampson, Natalie R. (Handbook of Social Sciences and Global Public Health, 2023)
Globally, air pollution accounts for approximately one in eight deaths, and diarrheal diseases account for one in nine child deaths annually. Lead exposure contributes to concerns of heart disease, stroke, and developmental intellectual disability. Further, across the world, nearly 23 million people are displaced by extreme weather events each year, which have been exacerbated by climate change and contribute to physical and mental health implications for entire communities. These and many other environmentally related experiences and their subsequent health outcomes are not experienced equally by race, ethnicity, or income, with Black, Brown, and Indigenous communities and low-income communities repeatedly experiencing the heaviest of burdens. Due to a variety of historic and contemporary policy and planning decisions, these patterns of environmental injustice persist on local, national, and global scales. In response, environmental justice (EJ) is a social movement, as well as a belief that people of all backgrounds deserve access to clean air and water and a healthy community in which to thrive. This chapter heavily focuses on the USA and its environmental health inequities, policies, and historic EJ movement. However, in our globalized society, EJ is a global issue that must be addressed as such by the field of public health.
Keywords: Cumulative impacts; Environmental justice; Health equity; Social determinants of health; Systemic racism; dept.pch

Period Poverty Among Black, Hispanic and Low-Income Communities in the United States: Challenges and Recommendations - Njoku, Anuli; Alhassan, Mubarak; Tohura, Sharaban; Garcia, Kayla (Hygiene, 2025)
Period poverty refers to the lack of access to or affordability of menstrual hygiene supplies such as sanitary products and the inaccessibility of washing facilities, waste disposal and educational materials. Period poverty can significantly affect menstruating individuals’ physical, mental, and reproductive health and emotional wellbeing; negatively impact educational outcomes; cause financial strain; result in absenteeism from work and school; create barriers to healthcare access; and perpetuate poor health outcomes for generations. Barriers to menstrual equity include lack of access to period support, cost, poor sanitary facilities, lack of education, social and cultural stigma, and legal restrictions. Therefore, it is crucial to actively advocate for initiatives to increase access to menstrual hygiene products, raise public awareness, and educate individuals on safe menstrual practices. Approximately 500 million girls and women worldwide and an estimated 16.9 million people in the United States experience period poverty, with the issue being particularly common among marginalized groups such as Black or Hispanic menstruating individuals and those who are homeless, living in poverty, of low income, or attending college. This article investigates the physical, psychological, educational and social impacts of inequitable access to menstrual products, menstrual education, and sanitation facilities among menstruating individuals who are Black, Hispanic or of low income within the United States. We examine the threat this poses to health equity and propose recommendations to address this pervasive issue.
Keywords: Absenteeism; Equity (law); Health care; Hygiene; Poverty; Public health; Sanitation; Socioeconomic status; dept.pch; environmental sustainability; gender disparities; health equity; menstrual education; menstrual health; menstrual health management; menstrual hygiene products; period poverty; period tax; polycystic ovarian syndrome (PCOS); poverty alleviation; women’s health

Racial and Ethnic Disparities in Chronic Stress among Male Caregivers - Unson, Christine; Njoku, Anuli; Bernard, Stanley; Agbalenyo, Martin (International Journal of Environmental Research and Public Health, 2023)
Whereas research on caregiving is well documented, less is known about gender inequalities in caregiver stress, coping mechanisms, and health outcomes, all of which may vary by race, ethnicity, and socioeconomic status. This scoping review investigated racial and ethnic disparities using the Stress Process Model among male caregivers. Several databases were searched including Academic Search Premier, Medline Complete, APA PsycInfo, CINHAL, Google, ProQuest, and Web of Science. Included were peer-reviewed articles in English, published from 1990 to 2022. A total of nine articles fulfilled inclusion criteria. Most of the articles indicated that compared to White male caregivers, African American male caregivers provided more hours of care, assisted with more activities of daily living (ADLs) and instrumental activities of daily living (IADLs), and experienced more financial stress. In terms of coping style, one study found African American male caregivers, compared to White male caregivers, held negative religious beliefs. Another study showed that they were at a higher risk for stroke than their White counterparts. The search revealed a dearth of studies on racial disparities in stress, coping, and health outcomes among male caregivers. Further research is needed on the experiences and perspectives of male minority caregivers. © 2023 by the authors.
Keywords: African American males; aging; caregiver burden; caregiving; coping; dept.pch; health and aging; health disparities; intersectionality; male caregiver; masculinity; older adults; peer-reviewed

Exploring Racism in Health Pedagogy - Evans, Marian; Breny, Jean; Njoku, Anuli; Searcy, Yan (Race and Pedagogy Journal: Teaching and Learning for Justice, 2022)
Keywords: dept.pch

Listen to the whispers before they become screams: addressing black maternal morbidity and mortality in the united states - Njoku, Anuli; Evans, Marian; Nimo-Sefah, Lillian; Bailey, Jonell (Healthcare, 2023)
Black women in the United States (U.S.) disproportionately experience adverse pregnancy outcomes, including maternal mortality, compared to women of other racial and ethnic groups. Historical legacies of institutionalized racism and bias in medicine compound this problem. The disproportionate impact of COVID-19 on communities of color may further worsen existing racial disparities in maternal morbidity and mortality. This paper discusses structural and social determinants of racial disparities with a focus on the Black maternal mortality crisis in the United States. We explore how structural racism contributes to a greater risk of adverse obstetric outcomes among Black women in the U.S. We also propose public health, healthcare systems, and community-engaged approaches to decrease racial disparities in maternal morbidity and mortality.
Keywords: COVID-19; black maternal mortality; dept.pch; health disparities; intersectionality; morbidity; peer-reviewed; pregnancy; race/ethnicity; racism; social determinants of health; weathering framework

Rural America and Coronavirus Epidemic: Challenges and Solutions - Ameh, Governor G.; Njoku, Anuli; Inungu, Jeff; Younis, Mustafa (European Journal of Environment and Public Health, 2020)
There are emerging concerns about the preparedness of rural communities in the United States in the face of the 2019 novel coronavirus (called SARS-CoV-2, causing the disease COVID-19) considering the existing disparities across the social determinants of health between rural and urban Americans. Taking into account the current exponential rate of spread of the coronavirus, this article critically examines the risk facing the 60 million Americans living in rural areas, discusses possible solutions pertaining to rural COVID-19 prevention, and examines measures to consider to prepare for this epidemic before it reaches rural areas.
Keywords: dept.pch; peer-reviewed

Transforming Dental Care: Integrating Geriatric Dentistry, Gerodontology, and Digital Marketing in Public Health - Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida; Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida (Digital Marketing for Public Dental Health: Global Impact Strategies, 2027)
The aging of the global population presents a significant challenge to public health, demanding innovative and sustainable dental approaches. This integrative literature review synthesizes research on the intersection of Geriatric Dentistry, Gerodontology, and digital marketing and communication str...

A Scoping Review of Skin Whitening Products: Users’ Knowledge and Motivations, Marketing Strategies, and Adverse Health Effects - Njoku, Anuli; Sawadogo, Wendemi; Pierce, Taryn; Albert, Kaleigh; Plummer, Fabian (International Platform of Registered Systematic Review and Meta-analysis Protocols, 2025)
Keywords: Adverse effect; Business; Marketing; Medicine; Pharmacology; dept.pch

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Exposure to Endocrine-Disrupting Chemicals and Early Onset of Menarche: A Systematic Review - Njoku, Anuli; Al-Hassan, Mousa; Tohura, Sharaban; Albert, Kaleigh; Pierce, Taryn; Sawadogo, Wendemi (Pollutants, 2025)
There has been a decline in the age at which girls experience menarche worldwide. Research suggests that exposure to endocrine-disrupting chemicals is linked to negative health consequences, including early onset of menarche. This systematic review examined the association between exposure to endocrine-disrupting chemicals (EDCs) and the early onset of menarche. Comprehensive searches of the PubMed, Embase, Web of Science, and Scopus databases were conducted to find relevant studies published from inception to November 2024. Exposure to certain EDCs, such as particulate matter and phthalates, showed significant associations with earlier menarche onset, while exposure to other EDCs (e.g., pyrethroids) was linked to delayed menarche timing. Overall, there were mixed findings in the relationships between various EDC exposures and menarche onset. Few studies investigated how exposure to EDCs and early menarche differed by race and ethnicity. This underscores the need for more studies that examine the relationship between early menarche onset and exposure to endocrine-disrupting substances. Education and policy approaches are also warranted to address this issue.
Keywords: Age of onset; Epidemiology; MEDLINE; Menarche; Risk assessment; Scopus; dept.pch; endocrine-disrupting chemicals; environmental health; menarche; puberty; reproductive health

Exploring healthcare workers’ intentions to volunteer in digital healthcare services for underserved communities: An extended TAM-based study - Almokdad, Eeman; Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed; Evans, Marian; Asanza, Dachel; Mouloudj, Smail (Electronic Journal of General Medicine, 2026)
Underserved communities face persistent challenges due to limited access to healthcare services. Digital volunteering offers opportunities for healthcare professionals to support these populations remotely. This study examined factors associated with healthcare workers’ intentions to participate in digital healthcare volunteering in Algeria. An extended technology acceptance model was used, incorporating perceived organizational support (OS), altruism, and social responsibility. A convenience sample of 142 healthcare workers completed a survey, and hierarchical regression analysis was conducted. Results indicated that perceived ease of use, social responsibility, altruism, perceived OS, and perceived usefulness were each significantly associated with intentions to engage in digital volunteering. The extended model explained 75.6% of the variance in intention, highlighting the relevance of psychological, organizational, and ethical factors. These findings provide insights for policymakers, healthcare organizations, and developers seeking to support digital volunteering initiatives. Limitations include the cross-sectional design and the use of convenience sampling, which may affect generalizability. Future research should consider longitudinal designs, larger and more diverse samples, and cross-cultural comparisons to validate and extend these findings.
Keywords: Affect (linguistics); Algeria; Digital health; Health care; Health professionals; Multilevel model; Relevance (law); Technology acceptance model; Variance (accounting); altruism; dept.pch; digital health; health disparities; health equity; healthcare access; organizational support; social marketing; social responsibility; telemedicine

Environmental Injustice and Electronic Waste in Ghana: Challenges and Recommendations - Njoku, Anuli; Agbalenyo, Martin; Laude, Janaya; Ajibola, Taiwo Folake; Attah, Mavis Asiwome; Sarko, Samuel Bruce (International Journal of Environmental Research and Public Health, 2023)
Electronic waste (e-waste) or discarded electronic devices that are unwanted, not working, or have reached their end of life pose significant threats to human and environmental health. This is a major concern in Africa, where the majority of e-waste is discarded. In the year 2021, an estimated 57.4 million metric tons of e-waste were generated worldwide. Globally, COVID-19 lockdowns have contributed to increased e-waste generation. Although Africa generates the least of this waste, the continent has been the dumping ground for e-waste from the developed world. The flow of hazardous waste from the prosperous ‘Global North’ to the impoverished ‘Global South’ is termed “toxic colonialism”. Agbogbloshie, Ghana, an e-waste hub where about 39% of e-waste was treated, was listed among the top 10 most polluted places in the world. The discard of e-waste in Ghana presents an issue of environmental injustice, defined as the disproportionate exposure of communities of color and low-income communities to pollution, its associated health and environmental effects, and the unequal environmental protection provided through policies. Despite the economic benefits of e-waste, many civilians (low-income earners, settlers, children, and people with minimal education) are exposed to negative health effects due to poverty, lack of education, and weak regulations. We critically examine the existing literature to gather empirical information on e-waste and environmental injustice. Comprehensive policies and regulations are needed to manage e-waste locally and globally.
Keywords: dept.pch; peer-reviewed

Determinants of Healthcare Professionals’ Intentions to Use Telemedicine for Elderly Care in Algeria: A Technology Acceptance Model Approach - Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed Chemseddine; Martínez Asanza, Dachel; Evans, Marian A.; Baviskar, Snehal (Geriatrics, 2026)
Background/Objectives: Telemedicine offers significant potential to improve the quality and accessibility of geriatric care, particularly in resource-constrained settings. However, its effective implementation depends largely on healthcare professionals’ acceptance and willingness to use such systems. Drawing on an extended Technology Acceptance Model (TAM), this study examines the determinants of doctors’ and nurses’ intentions to adopt telemedicine for elderly care in Algeria, with particular emphasis on self-efficacy and institutional support. Methods: This cross-sectional study employed a structured questionnaire administered to 130 healthcare professionals, including physicians and nurses, in Algeria. Hierarchical multiple regression analysis was conducted to test the proposed hypotheses and assess the incremental explanatory power of the extended model. Results: The extended TAM accounted for 48.7% of the variance in intention to use telemedicine. Institutional support (β = 0.432, p < 0.001) and self-efficacy (β = 0.264, p = 0.001) emerged as the strongest predictors. Perceived ease of use (β = 0.178, p = 0.038) and perceived usefulness (β = 0.139, p = 0.021) also had significant positive effects. The inclusion of self-efficacy and institutional support increased the model’s explanatory power by 23.5%. Conclusions: The findings highlight the critical role of organizational support mechanisms, digital competencies, and system usability in fostering telemedicine adoption among healthcare professionals. The study provides practical implications for policymakers and healthcare institutions, emphasizing the need for targeted training programs, supportive infrastructure, and institutional policies that enhance confidence and facilitate the integration of telemedicine into clinical workflows.
Keywords: Algeria; Technology Acceptance Model (TAM); cross-sectional study; dept.pch; digital health; elderly care; healthcare professionals; institutional support; self-efficacy; telemedicine

Using the protection motivation theory to examine the effects of fear arousal on the practice of social distancing during the COVID-19 outbreak in rural areas - Adunlin, Georges; Adedoyin, A. Christson A.; Adedoyin, Oreoluwa O.; Njoku, Anuli; Bolade-Ogunfodun, Yemisi; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2021)
The commentary elucidates the importance of Protection Motivation Theory (PMT) as a theoretical framework to encourage the practice of social distancing in rural areas as the world grappled with the pandemic of COVID-19 outbreak.
Keywords: COVID-19; Protection motivation theory; dept.pch; peer-reviewed; rural areas; social distancing

Climate Justice: Access to Safe Drinking Water and Health—A Legal Discourse - Njoku, Anuli U.; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Addressing the issues of water insecurity and unequal access to water has been a priority of the Sustainable Development Goals. Poor sanitation and inadequate access to drinking water are the second leading causes of death among children worldwide. Access to safe drinking water is a fundamental human right. Climate change represents one of public health’s greatest challenges and significantly exacerbates health disparities. According to the World Health Organization, approximately 3.6 billion people reside in areas highly vulnerable to the effects of climate change. Furthermore, climate change is anticipated to result in roughly 250,000 additional deaths each year between 2030 and 2050. In the United States, climate impacts such as severe storms and floods, escalating wildfires, extreme heat, poor air quality, and diminishing access to food and water disproportionately endanger Black, Brown, and Indigenous communities, low-income groups, people with disabilities, women, children, older adults, and others, making them more susceptible to the harmful health effects of climate change. The formulation and implementation of climate policies are essential to address the negative impacts of climate change. This chapter aims to: (a) describe the effects of climate change on access to safe drinking water; (b) emphasize the implications of climate change on drinking water disparities; (c) highlight policies to mitigate the effects of climate change; and d) discuss recommendations to tackle climate change and inequities in access to water. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Climate change; Environmental injustice; Health disparities; Water disparity; Water injustice; Water insecurities; Water scarcity; dept.pch

Investigating antecedents of intention to use green agri-food delivery apps: merging TPB with trust and electronic word of mouth - Mouloudj, Kamel; Aprile, Maria; Bouarar, Ahmed; Njoku, Anuli; Evans, Marian; Oanh, Le; Asanza, Dachel; Mouloudj, Smail (Sustainability, 2025)
The rapid expansion of digital platforms has significantly influenced consumer purchasing behaviors, particularly in the agri-food sector. Therefore, this paper investigates the key factors driving customers’ intention to use green agri-food delivery apps (GAFDAs) by integrating trust and electronic word of mouth (eWOM) into the Theory of Planned Behavior (TPB) framework. Additionally, this study examines gender as a moderating variable, assessing whether its influence alters the relationships between key determinants and behavioral intention. Data were collected from 252 Algerian consumers, and the proposed model was tested using SmartPLS 4 and SPSS 26.0. The results confirm that attitude, subjective norms, perceived behavioral control (PBC), trust, and eWOM positively and significantly influence the intention to use GAFDAs, with PBC emerging as the strongest predictor. Moreover, gender moderates the effect of trust on behavioral intention, with trust significantly influencing men’s adoption decisions but not those of females. In contrast, subjective norms and PBC are stronger predictors for female consumers. These findings highlight the importance of gender-specific marketing strategies to enhance GAFDA adoption. This study contributes to the literature by extending TPB with trust, eWOM, and gender moderation, offering valuable insights for marketers, policymakers, and app developers promoting sustainable food consumption.
Keywords: Advertising; Artificial intelligence; Business; Computer science; Control (management); Food delivery; Marketing; Psychology; Theory of planned behavior; Word of mouth; dept.pch

Modeling predictors of medication waste reduction intention in Algeria: extending the theory of planned behavior - Mouloudj, Kamel; Njoku, Anuli; Asanza, Dachel Martínez; Bouarar, Ahmed Chemseddine; Evans, Marian A.; Mouloudj, Smail; Bouarar, Achouak (International Journal of Environmental Research and Public Health, 2023)
COVID-19 caused an increase in the demand for medications, which led to an increase in pharmaceutical waste and there is no doubt that this contributes to environmental pollution. Hence, it became necessary to search for how to protect and improve the environment by encouraging the behavior of medication waste reduction. Accordingly, this study aims to investigate the factors affecting intentions to reduce medication waste. Considering this, we develop an extended theory of planned behavior (TPB) framework by incorporating the constructs of moral obligation, environmental awareness, and medication waste risk perception. Using the convenience sampling method and based on a self-administered questionnaire, a total of 225 usable responses were collected in five Algerian cities. The results showed that positive attitudes (β = 0.316, p < 0.001), moral obligation (β = 0.291, p < 0.001), environmental awareness (β = 0.227, p < 0.001), perceived behavior control (PBC) (β = 0.151, p = 0.001), greater perceived risks (β = 0.127, p < 0.001), and subjective norm (β = 0.096, p < 0.05) significantly and positively influence the medication waste minimization intention. Furthermore, our analyses revealed that the extended TPB model explained 73.40% of the intention variance. In conclusion, we have explored the intentions, and there may be a gap between intent and actual behavior. Therefore, we recommend future studies to examine the factors affecting the actual behavior of medication waste reduction and to investigate environmental ethics and religious commitment as predictors of waste reduction intentions.
Keywords: Africa; dept.pch; environmental health; environmental pollution; medication ecotoxicity; medication waste; moral obligation; peer-reviewed; perceived risk; pharmaceutical waste; theory of planned behavior; unused medications

Factors influencing the adoption of digital health apps: an extended technology acceptance model (TAM) - Mouloudj, Kamel; Bouarar, Ahmed Chemseddine; Asanza, Dachel Martínez; Saadaoui, Linda; Mouloudj, Smail; Njoku, Anuli U.; Evans, Marian A.; Bouarar, Achouak (Integrating Digital Health Strategies for Effective Administration, 2023)
Mobile health apps have been widely considered in the healthcare sector as innovative channels to reach patients and their families. Accordingly, the aim of the chapter was to investigate factors that influence the customers' adoption of digital health apps in Algeria. The authors adopted an extende...
Keywords: dept.pch

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities - Balasuriya, Lilanthi; Santilli, Alycia; Morone, Jennifer; Ainooson, Jessica; Roy, Brita; Njoku, Anuli; Mendiola-Iparraguirre, Andrea; O’Connor Duffany, Kathleen; Macklin, Bernard; Higginbottom, Jackson; Fernández-Ayala, Celina; Vicente, Genesis; et al. (JAMA Network Open, 2021)
Black and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic.To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities.This community-partnered qualitative study conducted semistructured, in-depth focus groups with Black and Latinx participants from March 17 to March 29, 2021, using a secure video conferencing platform. Participants were recruited through emails from local community-based organizations, federally qualified health centers, social service agencies, the New Haven, Connecticut, Health Department, and in-person distribution of study information from community health workers. A total of 8 focus groups were conducted, including 4 in Spanish and 4 in English, with 72 participants from a diverse range of community roles, including teachers, custodial service workers, and health care employees, in New Haven, Connecticut. Data were analyzed from March 17 to July 30, 2021.Interviews were audio-recorded, transcribed, translated, and analyzed using an inductive content analysis approach. Themes and subthemes were identified on the acceptability and accessibility of the COVID-19 vaccine among participants who identified as Black and/or Latinx.Among 72 participants, 36 (50%) identified as Black, 28 (39%) as Latinx, and 8 (11%) as Black and Latinx and 56 (78%) identified as women and 16 (22%) identified as men. Participants described 3 major themes that may represent facilitators and barriers to COVID-19 vaccinations: pervasive mistreatment of Black and Latinx communities and associated distrust; informing trust via trusted messengers and messages, choice, social support, and diversity; and addressing structural barriers to vaccination access.The findings of this qualitative study may impact what health care systems, public health officials, policy makers, health care practitioners, and community leaders can do to facilitate equitable uptake of the COVID-19 vaccine. Community-informed insights are imperative to facilitating COVID-19 vaccine access and acceptance among communities hardest hit by the pandemic. Preventing the further widening of inequities and addressing structural barriers to vaccination access are vital to protecting all communities, especially Black and Latinx individuals who have experienced disproportionate death and loss from COVID-19.
Keywords: Adolescent; Adult; African American; African Americans; Article; Black person; COVID-19 Vaccines; Connecticut; Female; Focus Groups; Health Services Accessibility; Hispanic; Hispanic Americans; Humans; Male; Middle Aged; Patient Acceptance of Health Care; SARS-CoV-2 vaccine; South and Central America; Trust; Young Adult; adolescent; adult; aged; community; content analysis; controlled study; coronavirus disease 2019; dept.pch; e-mail; employment; female; health auxiliary; health behavior; health care access; health care delivery; health care personnel; health care system; health center; health disparity; human; information processing; male; medical information; middle aged; outcome assessment; pandemic; patient attitude; peer-reviewed; public health service; qualitative research; risk factor; semi structured interview; social support; social worker; teacher; trust; vaccination; videoconferencing; young adult

Maternal Mortality Among Black Women in Brazil: A Retrospective Cohort Study - dos Santos, Gustavo; Njoku, Anuli; Mafetoni, Reginaldo; de Oliveira Sanfelice, Clara; Nicolau, Ana; Parenti, Patrícia; de Oliveira, Cely; López-Pedraza, Leticia; Mouta, Ricardo; Zihlmann, Karina; Lima, Cindy; Júnior, Cícero; et al. (International Journal of Environmental Research and Public Health, 2026)
BACKGROUND: Maternal mortality in Brazil remains a critical indicator of social and racial inequalities, reflecting structural failures in access to and quality of obstetric care. Black women, particularly those categorized as black or brown, are at a higher risk of dying during pregnancy, childbirth, or the postpartum period. This is the result of the intersection of institutional racism, poverty, and social vulnerabilities. This study aimed to analyze trends and associated factors of maternal mortality among black women in Brazil from 2000 to 2020. METHODS: This is a retrospective cohort analytical study using data from the Brazilian Mortality Information System. The sample included women aged 10 to 49 years whose underlying cause of death was classified under ICD-10 codes O00-O99. Descriptive and bivariate analyses were conducted, as well as Poisson and multinomial logistic regressions to estimate adjusted risk ratios according to skin color, education, region, type, and place of death. RESULTS: A total of 40,907 maternal deaths were identified, with 59.2% occurring among black women. The maternal mortality ratio was 39% higher among black women compared to white women and more than double among Indigenous women. Low education, residence in the North and Northeast regions, deaths outside hospital settings, and lack of formal investigation were independently associated with increased risk. Direct obstetric causes accounted for most deaths, with hypertensive disorders and puerperal complications being the leading conditions. CONCLUSIONS: Maternal mortality among black women in Brazil reveals deep structural inequalities. Urgent public policies that incorporate an intersectional perspective, addressing race, gender, and class, are necessary to reduce disparities and ensure equitable and dignified maternal healthcare.
Keywords: Black women; Cohort study; Inequality; Maternal health; Maternal morbidity; Public health; Retrospective cohort study; dept.pch

Racial Disparities and the Use of Artificial Intelligence for Predicting Maternal Mortality: A Literature Review - Gonçalves dos Santos, Gustavo; Njoku, Anuli; Mass, Ana Carolina Pereira; Ribeiro, Ellen Eduarda Santos; Oliveira, Letícia Eduarda de; Lima, Maria Julia Cunha Silva; Ferro, Taís de Abreu; Pirozi, Lilian Reinaldi Ribeiro; Peregrino, Antônio Augusto de Freitas; Santos, Célia Maria Pinheiro dos; Viana, Lucia Helena Ferreira; Sousa, Marilda Gonçalves de; et al. (Epidemiologia, 2026)
Background: Maternal mortality remains a major global health challenge, disproportionately affecting black and Indigenous women. Hypertensive disorders of pregnancy and postpartum hemorrhage are the leading direct causes of maternal death. Artificial intelligence (AI) tools have emerged as potential strategies for predicting these complications, yet concerns persist about their equity and validation across racial groups. Methods: A rapid review was conducted in five databases, PubMed, EMBASE, Web of Science, Scopus and LILACS, to synthesize recent evidence on the use of AI for preventing maternal mortality due to hypertension and postpartum hemorrhage. Studies published in the last five years that included racial or ethnic data were selected and analyzed narratively. Results: Ten studies met the inclusion criteria, showing high predictive accuracy of AI models (AUROC often >0.95) for severe maternal outcomes. However, few models incorporated racial variables or underwent external validation in racially diverse or low-resource populations. Evidence suggests that unrepresentative datasets may perpetuate or exacerbate existing health inequities. Conclusions: AI demonstrates strong technical performance in predicting maternal complications but limited equity in application. Broader racial representation, external validation, and ethical governance are essential for ensuring that AI-based tools reduce rather than reinforce racial disparities in maternal mortality.
Keywords: artificial intelligence; dept.pch; hypertension; maternal mortality; postpartum hemorrhage; racial disparities in health